Collisions of Two-Phase Liquid Droplets in a Heated Gas Medium - Pavel Tkachenko (MDPI AG, 2021)
The paper presents the experimental research findings for the integral characteristics of processes developing when two-phase liquid droplets collide in a heated gas medium. The experiments were conducted in a closed heat exchange chamber space filled with air. The gas medium was heated to 400–500 °C by an induction system. In the experiments, the size of initial droplets, their velocities and impact angles were varied in the ranges typical of industrial applications. The main varied parameter was the percentage of vapor (volume of bubbles) in the droplet (up to 90% of the liquid volume). The droplet collision regimes (coalescence, bounce, breakup, disruption), size and number of secondary fragments, as well as the relative volume fraction of vapor bubbles in them were recorded. Differences in the collision regimes and in the distribution of secondary fragments by size were identified. The areas of liquid surface before and after the initial droplet breakup were determined. Conditions were outlined in which vapor bubbles had a significant and, on the contrary, fairly weak effect on the interaction regimes of two-phase droplets.